2013
DOI: 10.1080/08974438.2013.723997
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Halal Awareness, Halal Certification, and Marketing Components in Determining Halal Purchase Intention Among Non-Muslims in Malaysia: A Structural Equation Modeling Approach

Abstract: Although the important role of halal awareness, halal certification, and marketing-related components in determining purchase intention has been recognized in the marketing literature, empirical examination of this issue is limited. In order to fill this knowledge gap, this study aimed to determine the relationships between halal awareness, halal certification, food quality, marketing promotion, and brand with the intention to purchase halal product among the non-Muslim community in Malaysia. The data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
552
3
47

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(642 citation statements)
references
References 23 publications
40
552
3
47
Order By: Relevance
“…Namkung and Jang (2007) also showed that food quality has a positive influence on behavioral intention. According to Aziz and Chok (2013), halal food should be recognized that the high quality by the non-Muslim consumers, which has an impact on purchase intention. Therefore, we hypothesize that:…”
Section: Halal Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Namkung and Jang (2007) also showed that food quality has a positive influence on behavioral intention. According to Aziz and Chok (2013), halal food should be recognized that the high quality by the non-Muslim consumers, which has an impact on purchase intention. Therefore, we hypothesize that:…”
Section: Halal Qualitymentioning
confidence: 99%
“…In addition, Mohamed, Shamsudin, and Rezai (2013) observed that if consumers lack knowledge about halal food may affect their attitude and purchase intention. In Aziz and Chok (2013), the quality of halal food can be a source of product differentiation and is an important parameter for the food industry; therefore, understanding the relationship between the quality of halal food and consumer behavior is very important for producer and marketers. Many previous studies have been focused on the purchase intention towards halal food among young Muslim consumers (Khalek, 2014;Musa, 2014) but there are very few studies that focus on young non-Muslim consumers.…”
Section: Introductionmentioning
confidence: 99%
“…All variables in this measurement model meet the criteria of discriminant validity. Thus, this instrument confirms discriminant validity and the individual variable will not measure the same thing [24], [32].…”
Section: Discriminant Validitymentioning
confidence: 93%
“…AVE value in the last column of Table II presents convergent validity of construct. The construct are considered valid when the AVE of each construct higher than 0.5 [32]. In Table II, all constructs have AVE is ranging from 0.51 to 0.66 that are valid except consumers' purchasing (AVE = 0.42).…”
Section: B Construct Reliability and Convergent Validitymentioning
confidence: 99%
See 1 more Smart Citation